Design and parameter evaluation of ejector refrigeration cycle system - Lu, Yuwen. (2013)
An experimental ejector refrigeration system is designed and constructed to study the performanceofR134a as working fluid in this project. The influence of evaporator, generator, and condenser temperatures on the system performance is studied. The experimental results demonstrate that the entrainment ratio and coefficient of performance of the system increase with increasing of the evaporator temperature, and the coefficient of performance increases with increasing of the generator temperature over a range of operating conditions.